Effects of different feedback variants on pacing adherence in a field based running test - Dobiasch, M.; Stafylidis, S.; Baca, A. (International Journal of Performance Analysis in Sport, 2021)
Running field tests are utilised to assess the athlete`s fitness level with high specificity. However, in graded exercise tests the lack of speed control can result in an uneven pace, reducing reproducibility and accuracy. The purpose of this study was to develop feedback variants (FV) and investigate their effect on the athlete`s ability to keep the pace constant. Forty-eight participants completed four trials of a Conconi test (randomised) over four paces (7.5 - 10 km·h-1). A smartphone app provided athletes with four FVs: Classic, Sound (verbal), Vibration, and Sound & Vibration. We found a significant effect of FV on adherence (defined as time within 0.3 km·h-1 of target speed): F(3,141) = 41.45, p < .001, ?2 = .268. Adherence in Classic (M± SD) 39.51 ± 13.51% was significantly lower (p < .001) than in Vibration (53.24 ± 14.98%), Sound (60.34 ± 11.21%) and Sound & Vibration (59.17 ± 15.17%). The novel FV provided better adherence compared to the conventional method, with Sound and Sound & Vibration showing the highest adherence. Generally, the novel FVs have the advantage of being easily implemented and decreasing the required time for setup, data collection and processing, therefore proving useful in conducting field performance tests.